Bharatiya Vidya Bhavan (2003)
[Dt.:] Das 'Institute of Indian Art and Culture - Bharatiya Vidya Bhavan UK' hat sich zum Ziel gemacht, die Lehre und das Verständnis für die indische Kunst und Kultur als integraler Teil der britischen Kultur, zu erhalten und zu fördern. Es sieht sich als ein Bildungszentrum, welches seinen Fokus auf die folgenden Bereiche gelegt hat: Kunst, Archäologie, Theater, Tanz, musische Erziehung, Sprachen und Yoga. - [Engl.:] The 'Institute of Indian Art and Culture - Bharatiya Vidya Bhavan UK' has the aim to preserve and to promote the teaching and understanding of Indian art and culture as an integrated part of the British culture. It views itself as an educational institution, laying its focus on following areas: art, archeology, theater, dance, musical education, languages and yoga.